Significant weed species, density and frequency in sesame cultivated areas of middle Shabelle Province in Somalia - Hussein Ahmed Nur Yusuf; Ahmed Abdiaziz Alasow; Hüsrev Mennan (Acta Agriculturae Scandinavica. Section B, Soil and Plant Science)
Weed competition represents a major constraint to sesame (Sesamum indicum L.) productivity, with yield losses of up to 90% reported due to uncontrolled weed infestations. However, comprehensive information on the weed flora in sesame fields is lacking, particularly in Somalia where the crop plays a vital economic and food security role. In this study, we conducted surveys across 36 sesame production areas in Middle Shabelle province, a key sesame-growing region of Somalia. Accordingly, twenty-seven weed species from 14 plant families were identified infesting the surveyed sesame fields. The results show that the most prevalent and problematic weeds in terms of density were Cynodon dactylon (2.15 plants/m2), Portulaca oleracea (1.71 plants/m2), Cyperus rotundus (1.58 plants/m2), Heliotropium steudneri (0.99 plants/m2), and Xanthium strumarium (0.87 plants/m2). The most prevalent species were Cynodon dactylon (40.70%), Xanthium strumarium (40.50%), Portulaca oleracea (37.42%), Heliotropium steudneri (35.90%), and Cyperus rotundus (26.85%). Furthermore, face-to-face interviews with 50 farmers demonstrated that most producers favour hand hoeing as the primary method for weed control. By characterising the major weed species and their population dynamics, this study provides critical foundational data to inform the development of integrated weed management strategies for enhancing sesame productivity and food security in the region.